A multitaxonomic assessment of Natura 2000 effectiveness across European biogeographic regions - Lorenzo Ricci; Michele Di Musciano; Francesco Maria Sabatini; Alessandro Chiarucci; Piero Zannini; Roberto Cazzolla Gatti; Carl Beierkuhnlein; Anna Walentowitz; Alexandra Lawrence; Anna Rita Frattaroli; Samuel Hoffmann (Conservation Biology, 2024)
The Natura 2000 (N2K) protected area (PA) network is a crucial tool to limit biodiversity loss in Europe. Despite covering 18% of the European Union's (EU) land area, its effectiveness at conserving biodiversity across taxa and biogeographic regions remains uncertain. Testing this effectiveness is, however, difficult because it requires considering the nonrandom location of PAs, and many possible confounding factors. We used propensity score matching and accounted for the confounding effects of biogeographic regions, terrain ruggedness, and land cover to assess the effectiveness of N2K PAs on the distribution of 1769 species of conservation priority in the EU's Birds and Habitats Directives, including mammals, birds, amphibians, reptiles, arthropods, fishes, mollusks, and vascular and nonvascular plants. We compared alpha, beta, and gamma diversity between matched selections of protected and unprotected areas across EU's biogeographic regions with generalized linear models, generalized mixed models, and nonparametric tests for paired samples, respectively, for each taxonomic group and for the entire set of species. PAs in N2K hosted significantly more priority species than unprotected land, but this difference was not consistent across biogeographic regions or taxa. Total alpha diversity and alpha diversity of amphibians, arthropods, birds, mammals, and vascular plants were significantly higher inside PAs than outside, except in the Boreal biogeographical region. Beta diversity was in general significantly higher inside N2K PAs than outside. Similarly, gamma diversity had the highest values inside PAs, with some exceptions in Boreal and Atlantic regions. The planned expansion of the N2K network, as dictated by the European Biodiversity Strategy for 2030, should therefore target areas in the southern part of the Boreal region where species diversity of amphibians, arthropods, birds, mammals, and vascular plants is high and species are currently underrepresented in N2K.